The effect of immunosuppressive agents on the induction of nuclear factors that bind to sites on the interleukin 2 promoter (The Rockefeller University Press, 1990)
Cyclosporin A (CSA), FK506, and glucocorticosteroids all inhibit the production of lymphokines by decreasing lymphokine gene expression. Previous experiments have defined six different sites that may contribute to the transcriptional control of the interleukin 2 (IL-2) promoter, and for each, active nuclear binding factors are induced upon mitogenic stimulation. While dexamethasone markedly blocks the increase in IL-2 mRNA in stimulated human blood T cells, we found that the drug does not block the appearance of factors that bind to the transcriptional control sites termed AP-1, AP-3, NF-kB, OCT-1, B site, and NF-AT. In contrast, both CSA and FK506 have similar effects: the drugs cause modest decreases in AP-3 and NF-kB, and markedly decreases in the activity of AP-1 and NF-AT. Therefore, CSA and FK506, while chemically different, seem to act upon a similar pathway that leads to IL-2 gene expression, whereas glucocorticoids do not affect this pathway.